1999
DOI: 10.1046/j.1365-246x.1999.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

A seismic cross-section through the east European continent

Abstract: S U M M A RYA 2-D pro¢le for the shear wave velocity and anisotropy between Egypt and Spitsbergen is presented. The pro¢le is constructed using fundamental-and higher-mode Love and Rayleigh waves recorded by stations of the NARS-DEEP, IRIS and GEOFON networks. The surface wave data have been inverted for shear velocity and anisotropy using a waveform inversion. In the eastern Mediterranean lithosphere we observe a large di¡erence (7 per cent) between SH and SV velocities. We interpret this anomaly as an anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…and inversion of Pn travel times [e.g., Hearn , 1999]. Information on polarization anisotropy is available only for the easternmost Mediterranean basin [ Muyzert et al , 1999], where up to 7% anisotropy is observed in the lithosphere, and for the Iberian Peninsula [ Maupin and Cara , 1992], where anisotropy is required only below 100 km.…”
Section: Introductionmentioning
confidence: 99%
“…and inversion of Pn travel times [e.g., Hearn , 1999]. Information on polarization anisotropy is available only for the easternmost Mediterranean basin [ Muyzert et al , 1999], where up to 7% anisotropy is observed in the lithosphere, and for the Iberian Peninsula [ Maupin and Cara , 1992], where anisotropy is required only below 100 km.…”
Section: Introductionmentioning
confidence: 99%
“…It is absent from some regions, for example, northern Europe (Muyzert et al, 1999). The values of x $ 1.08, corresponding to 4% difference in SH and SV velocity, are however very common below the Moho and down to at least 200 km depth (Freybourger et al, 2001;Gaherty, 2007;Marone et al, 2004;Panning and Romanowicz, 2006) (see Figure 19 for some examples).…”
Section: Surface Waves and Upper Mantlementioning
confidence: 99%
“…Similarly both the Australian and Kaapvaal cratons were found to have a uniform 4–5% shear anisotropy in the lid extending to 250 km depth with a sharp transition to an isotropic mantle regime below that [ Gaherty et al , 1999; Simons et al , 1999; Jordan et al , 1999]. Significantly, however, the results of the NARS profile through the east European continent identified large shear anisotropy (7%) beneath the Mediterranean, but no clear pattern in shear anisotropy beneath the EEP [ Muyzert et al , 1999]. …”
Section: Comparison With Other Cratonic Modelsmentioning
confidence: 99%
“… Marquering and Snieder [1996] found a relatively laterally homogenous, fast S wave velocity structure beneath the platform extending to 300 km depth. This is also apparent in the 2‐D profile from the NARS experiment which shows a sharp transition in the thickness of the lithospheric root between the EEP (200 km) and younger continental regions (100 km) [ Muyzert et al , 1999; Paulssen et al , 1999]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation